Implementasi Asas Legalitas dalam Pasal 34 Qonun Jinayat - Fathi Yakan A; M Ilham Agustian; Deden Najmudin (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This article examines the implementation of the principle of legal certainty or legality in the Qanun Jinayat, specifically Article 34, a regulation of Islamic criminal law in Aceh. This research is motivated by differing views regarding the application of the Qanun Jinayat, particularly regarding the principle of legality, a fundamental principle in modern criminal law. The principle of legality, which states that "there is no punishment without law," aims to protect individuals from arbitrary actions by those in power. However, in the context of the Qanun Jinayat, it is questionable whether this regulation fully accommodates these concerns. This research uses a normative legal research method with a conceptual and regulatory approach. Data were collected through literature review, legal document analysis, and interpretation of articles in the Qanun Jinayat. The results indicate that the Qanun Jinayat has attempted to adopt the principle of legality by clearly defining prohibited acts (jarimah).